Model Pemberdayaan Laboratorium Bank Mini Syariah di Perguruan Tinggi - Eva Fauziah; Ifa Hanifia Senjiati; Sandy Rizki Febriadi (IAIN Salatiga, 2017)
Sharia Mini Bank Laboratory is a medium to implement Tri Dharma of College which is expected to contribute to accelerate the development of sharia in Indonesia. Therefore, empowerment of laboratory of bank mini syariah as a place to develop competence in intellectual, motor skill and skill to use Islamic banking tools for increasing the competence of graduate and sharia banking students need to be reviewed. This is a qualitative research. Method of collecting data is using deep data observation technique. Data analysis is using spradley model domain analysis. Theresults showed that the model of empowerment of Mini Sharia Bank laboratory in Higher Education has four models; they are 1) model of secondary empowerment, 2) model primary internal empowerment of student, 3) model of primary internal empowerment of student and lecturer and 4) model of primary external empowerment. This laboratory empowerment model is based on observations at four universities in Java, namely Bandung Islamic University (UNISBA), Islamic University of Malang (UNISMA), UIN Malang and UIN Sunan Ampel Surabaya.Laboratorium Bank Mini Syariah merupakan sarana penunjang dan pelaksana program Tri Dharma Perguruan Tinggi yang diharapkan mampu memberikan kontribusi untuk mengakselerasi perkembangan syariah di Indonesia. Oleh karena itu, pemberdayaan laboratorium Bank Mini Syariah sebagai tempat mengembangkan kompetensi baik dalam bidang intelektual, ketrampilan motorik dan terampil memggunakan alat-alat media perbankan syariah untuk peningkatan kompetensi mahasiswa lulusan keuangan dan perbankan syariah perlu ditelaah. Metode penelitian menggunakan metode kualitatif dengan teknik pengumpulan data observasi mendalam. Analisis data menggunakan analisis domain model spradley. Hasil penelitian menunjukkan bahwa model pemberdayaan laboratorium Bank Mini Syariah di Perguruan Tinggi memiliki empat model yaitu 1). Model pemberdayaan sekunder, 2). Model pemberdayaan primer internal mahasiswa, 3). Model pemberdayaan primer internal mahasiswa dan dosen, dan 4). Model pemberdayaan primer eksternal. Model pemberdayaan laboratorium ini berdasarkan pengamatan pada empat perguruan tinggi di Jawa yaitu Universitas Islam Bandung, Universitas Islam Malang, UIN Malang dan UIN Sunan Ampel Surabaya.